2017
DOI: 10.1038/s41598-017-04761-y
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of altered feedback learning in women recovered from anorexia nervosa

Abstract: Anorexia nervosa (AN) is associated with exaggerated self-control and altered reward-based decision making, but the underlying neural mechanisms are poorly understood. Consistent with the notion of excessive cognitive control, we recently found increased dorsal anterior cingulate cortex (dACC) activation in acutely ill patients (acAN) on lose-shift trials in a probabilistic reversal learning (PRL) task. However, undernutrition may modulate brain function. In attempt to disentangle trait from state factors, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 100 publications
4
16
0
Order By: Relevance
“…Functional neuroimaging studies of simple reward processing and cognitive control have documented persistent alterations in weight-recovered patients with anorexia nervosa, 4,45,46 but few fMRI studies in the domain of rewardrelated decision-making (other than delay discounting studies discussed below) have focused on this population. Similar to the current findings of no group differences in dACC function in weight-recovered patients with anorexia nervosa, Ritschel and colleagues 47 found (in contrast to acutely underweight patients 48,49 ) no group differences in dACC response to negative feedback in a decision-making task that required participants to adapt choice behaviour to changing reward contingencies.…”
Section: A Dacc Activationsupporting
confidence: 87%
“…Functional neuroimaging studies of simple reward processing and cognitive control have documented persistent alterations in weight-recovered patients with anorexia nervosa, 4,45,46 but few fMRI studies in the domain of rewardrelated decision-making (other than delay discounting studies discussed below) have focused on this population. Similar to the current findings of no group differences in dACC function in weight-recovered patients with anorexia nervosa, Ritschel and colleagues 47 found (in contrast to acutely underweight patients 48,49 ) no group differences in dACC response to negative feedback in a decision-making task that required participants to adapt choice behaviour to changing reward contingencies.…”
Section: A Dacc Activationsupporting
confidence: 87%
“…It is conceivable that a conflict between external instruction (avoid unhealthy food), and internal impulse (approach unhealthy food) increases activity of the rAG in order to solve this conflict. This is consistent with studies showing that the rAG is directly engaged in resolution of stimulus-response conflicts, but also attentional reorientation and response inhibition 32-37 .…”
Section: Discussionsupporting
confidence: 92%
“…Since the last review in 2016, an additional six studies have been found that examined WM in AN ( Phillipou et al, 2015 ; Biezonski et al, 2016 ; Giombini et al, 2016 ; Bentz et al, 2017 ; Ritschel et al, 2017 ; Solstrand Dahlberg et al, 2017 ). Of these six studies, none reported better WM performance in AN compared to HC; some reported normalization of WM function after treatment such as cognitive remediation therapy (CRT) and in-patient treatment ( Castro-Fornieles et al, 2010 ; Giombini et al, 2016 ), whereas others show that abnormal function remains on recovery ( Ritschel et al, 2017 ). This leaning toward the reporting of worse WM performance in AN may reflect the fact that there may be heightened WM capacity in AN but that this is utilized primarily for the exercising of detailed, rigid, complex cognitions about eating-related concerns.…”
Section: Anorexia Nervosa Working Memory and Cognitive Controlmentioning
confidence: 99%